Role of Proteus mirabilis DNA in Comparison to Candida albicans DNA in Rats’ Joints Infection - Kadhim, Ahmed F.; AL-Mathkury, Harith J.; Obaid, Hind H. (Iraqi Journal of Science, 2023)
In This study a comparison between Proteus mirabilis DNA and Candida albicans DNA in Arthritis. Fourteen Proteus isolates (11.6%) were collected from 120 specimens collected from midstream urine of patients of both sex and different ages attending different hospitals in Baghdad. Antibiotic sensitivity assay showed that All Proteus mirabilis recovered from UTI developed multidrug resistance and variable degree of resistance. Histopathological changes in model treated with Proteus mirabilis DNA revealed congestion, inflammatory cells infiltration, oedema, hemorrhagic exudates as well as necrotic cells. Furthermore, articular joints damage has been noticed with articular tissue in ligament and lining epithelium. In addition, an aggregation of lymphocyte was observed as well. While rats treated with Candida albicans DNA depict a congestion and a mild infiltration of inflammatory cells with oedema and augmented infiltration reaction inside the joint space. Serum Interleukine-6 (IL-6) levels peaked within 24 hours after injection of P. mirabilis DNA intraarticularly, while serum IL-6 levels did not increase in rats injected with C. albicans DNA and TE. The serum level of Anti-double strand antibody IgM (Anti-ds Ab) was assessed after 14 days and results revealed that Anti-ds Ab concentration was significantly higher (P< 0.01) in the animal model treated with Proteus mirabilis DNA than those treated with Candida albicans DNA. Total white blood cell count has been assessed, Animal model treated with 30μg/100 μl P. mirabilis DNA showed a significant (P< 0.05) increasing in total count of WBC, while there were insignificant differences between animals treated with 30μg/100 μl C. albicans and control animal.